THE INFLUENCE OF PLACE-BASED SOCIAL DETERMINANTS OF HEALTH ON TEMPORAL CHANGES IN CARDIOVASCULAR MORTALITY - Katrina Terry; Mohamed Makhlouf, MD; Salah E Altarabsheh; Mellissa Zullo; Vaishali Deo; Fanny Petermann-Rocha; Yakov Elgudin; Khurram Nasir; Sanjay Rajagopalan; Sadeer Al-Kindi; Salil Deo, MD (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD Risk Reduction Background: Increased place-based social deprivation is known to be associated with higher cardiovascular mortality (CVM) rates. While CVM rates in the US have been declining overall, our study evaluated whether this holds true for areas with increased social deprivation. Methods: In this cross-sectional study, we used county-level CVM rates between 2000 and 2019 and linked it to the CDC Social Vulnerability Index (SVI), and analyzed data from 3052 counties nationwide. We grouped counties as per their SVI (Group I 0 - 0.2, Group II 0.21 - 0.4, Group III 0.41 - 0.6, Group IV 0.61 - 0.8,and Group V 0.81 - 1) and obtained the relative change in the age adjusted CVM between 2000-2003 and 2016-2019. We studied the temporal change in CVM across SVI groups, overall and separately according to race (white vs black), sex (men vs women) and county location (metro vs non-metro). We used adjusted linear regression analyses to explore the association between increasing SVI and the relative change in CVM. Results: The median county-level age-adjusted CVM (aa-CVM) rate (per 100,000) overall was 272.6 [IQR: 237.5, 311.7]. Men (315.6 [IQR: 273.4, 363.9]) had higher aa-CVM rates than women (221.3 [IQR: 189.6, 256.7]), and blacks (347.2 [IQR: 301.1, 391.1]) had higher aa-CVM rates than whites (258.9 [IQR: 226, 299.1], p < 0.001). The aa-CVM for SVI I (233.6 [IQR: 214.8, 257.0]) was significantly higher than group V (323.6 [IQR: 277.2, 359.2], p < 0.001). The relative reduction in CVM was significantly higher for SVI group I (32.2% [IQR: 24.2%, 38.4%]) than SVI group V (27.2% [IQR: 19%, 34.1%]) counties. An increasing SVI index was associated with lower relative percent decline in the age-adjusted CVM (model coefficient -6.01 [0.73], p < 0.001). Conclusions: We observed higher age-adjusted CVM in more socially deprived counties in the US. While the overall age-adjusted CVM has declined in the past 20 years, this improvement is substantially lesser in more socially deprived counties.